Páginas singulares: propagandas de cigarro na revista Ilustração Brasileira - Lopes, Lara (2014)
This study aims to analyze the construction of cigarette advertisements that were published in Ilustração Brasileira magazine. These singular pages contains photographs of women holding a cigarette and texts that tend to associate the act of smoking to beauty, elegance and \"modernity.\" Although they clearly promote cigarette, there is no mention to brands or advertisers in these pages, making it a part of the magazine, like any other section, with regular frequency and constant publishing. Therefore, we intend to understand the construction of these pages through two strands: the relationship between advertisement published in the magazine and the advertiser; and advertising as a language that seeks to establish habits, gestures and behavior through the association of text and images.